MIXING OF UPPER SEDIMENT LAYERS BY BENTHIC ORGANISMS - Kuptsov V.M. (My University, 1989)
The postsedimentation process of greatest extent in the ocean, occurring nearly everywhere, is mixing of the upper layer of bottom sediments by benthic organisms. The number of radioactive elements with steady fluxes into the sediments that can be used to determine the mixing characteristics is comparatively small. The elements that can now be used for the purpose are the cosmogenic isotopes 7Be, 32Si and 14C, and the natural radioactive elements 234Th and 210Pb. We show examples of the use of these isotopes to determine the diffusion coefficient. These examples well illustrate that these isotopes can be used to determine diffusion coefficients over a wide range of values.